FinTech Services Adoption in Greece: The Roles of Trust, Government Support, and Technology Acceptance Factors - Stefanos Balaskas; Maria Koutroumani; Kiriakos Komis; Maria Rigou (FinTech, 2024)
Financial technology or FinTech is a term that has arisen in recent years; it refers to innovative technologies designed to enhance and automate the provision and utilization of financial services. Its solutions aim to simplify conventional financial procedures, boost automation, lower expenses, and deliver personalized and user-friendly experiences for both businesses and consumers. But this question remains: what drives users to adopt such services and how are they perceived by the general public? In our study, a quantitative non-experimental correlational methodology in the form of an online survey was utilized to study the Greek citizens’ behavioral intentions regarding the utilization of FinTech services. Based on the answers of 348 respondents, structural equation modeling was performed to evaluate the theoretical model, which included technology acceptance factors. Unlike conventional models that primarily relate user acceptance to adoption, our research goes beyond these models by expanding on the TAM model via an exploration of the role of trust and the influence of government support on user trust and perceived effort and an examination of how these, in turn, impact the FinTech services adoption. In our context, government support refers to the regulatory frameworks, policies, and endorsements provided by governmental bodies. The results indicated that all the aspects of this study related to trust and user acceptance (effort expectancy and performance expectancy) revealed a significant and positive relationship with FinTech services adoption and can be predictive factors of citizens’ future intentions to use FinTech services. This study also verified that trust in FinTech services mediates the relationship between government support and FinTech services adoption. We place emphasis on the intricate yet complex decision-making process in technology adoption, particularly in the field of FinTech, by exploring the intertwined relationships of trust, government support, and technology acceptance factors; the findings offer valuable insights for policymakers and industry practitioners.